ANALISIS PENGEMBANGAN OBJEK WISATA TANJUNG KARANG DI KECAMATAN BANAWA KABUPATEN DONGGALA - Indonesiani, Dewi Yanti Ratih (Katalogis, 2015)
The purposes of this study are: (1) analyzing the development of tourist attractions Tanjung Karang in sub district Banawa, District Donggala. The main theory of tourist attraction development that researcher adopts is the theory of organizational development of Victor H. Vroom and Philip Yelton in Gibson (2000: 241) which includes; (1) Environmental Factors (2) Internal factors. The research method used is descriptive qualitative approach. The research takes place at Tourist attraction Tanjung Karang area in dub district Banawa, district Donggala with seven informants selected purposively. Data collection was conducted using interview, observation, and documentation. Data were analyzed using the SWOT analysis model (Strength, Weakness, Oppportunity, and Threat) in Salusu (2000.350). Tourist Attractions Tanjung Karang Development as a Tourism Village is not maximal. This can be seen from the environmental factors and internal factors that have not been optimal. Both of these aspects have not been performed well as expected. Environmental factors which have been owned by tourist attraction Tanjung Karang is recognized to have weaknesses in services, it has not been able to provide adequate cottage rooms; Power installation and clean water installation are not sufficient; an inadequate number of police officer to maintain security around the tourist attraction; an inadequate information center or tour guide office and unavailability health services either health centers nor hospitals, also the sanitation is unmaintained tourist attractions area Tanjung Karang. Tourist attraction development as a tourist village is not only supported by the village and the local government, but it is also supported by the society from community leaders, youth, students, as well as merchants to contribute according to their ability and expertise. Infrastructure is already sufficient, all level of society is being serious preparing this tourist village. Support from the government and the community to develop tourism village is quite reasonable because the village Tanjung Karang meets the standards as a beautiful tourist village, safe, comfortable, natural, and has a strong attraction supported by facilities and infrastructure. Besides those supports, society supports also becomes strength in developing tourist attraction Tanjung Karang as a tourist village that is always crowded with tourists.